Control of sexual maturation and growth in Atlantic cod (Gadus morhua) by use of cold cathode light technology - Figueiredo, Filipe André Moreira de, 1984- (2013)
The once abundant stocks of Atlantic cod in the North Atlantic have declined and now the fisheries are either severely restricted or even closed in order to preserve the remaining stocks. As a result, there is a growing interest in cod aquaculture to bridge the gap between decreasing supply and increasing demand. Profitable aquaculture of Atlantic cod is, in part, limited by early sexual maturation which slows or arrests growth and reduces flesh quality. Aquaculture cod mature earlier than wild fish. The main environmental factors that determine the time of maturation of cod are food availability, temperature and photoperiod. The decreasing day-length during autumn acts as a cue for the cod to initiate the maturation process. Therefore, it may be possible to prevent precocious maturation with extended photoperiods during the latter half of the year. The present work tests the effect of a Cold Cathode Light system (CCL). The spectral composition of the CCL light penetrates water well and matches the light perception of the cod. The cod were exposed to continuous light from the lamps in cages for two years, while a control group was reared under natural photoperiod. The results show that the light treatment arrested or delayed maturation for 1 or 2 months, depending on the sex and age of the fish. The fish exposed to the light treatment weighed 11% more than the control group. Even though the exposure to continuous light influenced sexual maturation and improved growth performance, the degree of improvement is not considered to be sufficient to make cod aquaculture attractive from an economic standpoint. Stofnstærð Atlantshafsþorsks, sem áður veiddist í miklu magni í norðurAtlantshafi, hefur minnkað á síðustu áratugum og nú eru veiðar úr flestum stofnum takmarkaðar eða bannaðar. Aukin eftirspurn eftir þorski hefur orðið til þess að áhugi fyrir þorskeldi hefur aukist til muna. Ótímabær kynþroski hefur neikvæð áhrif á arðsemi þorskeldis vegna þess að við hrygningu hægir á vexti og holdgæði verða lélegri. ...